The Effect of Peer Education on Adolescent Community Empowerment in Efforts to Prevent Early Marriage Among Vulnerable Adolescents (PT. LARPA JAYA PUBLISHER, 2024)
Early marriage remains a significant social issue in Indonesia, particularly among vulnerable adolescents who are at risk of engaging in dating and premarital sexual behaviors. This study aimed to examine the effect of peer education on community empowerment in preventing early marriage among vulnerable adolescents in Bandung Regency. A quasi-experimental design with a pretest-posttest approach was employed, involving 82 adolescents divided equally into intervention (peer education) and control (lecture) groups. Data were collected using validated questionnaires measuring knowledge of early marriage and analyzed using paired t-tests. The findings showed a significant increase in knowledge scores in the intervention group from 58.2 ± 10.5 to 78.6 ± 9.3 (p < 0.001), while the control group showed a smaller increase from 57.9 ± 11.2 to 63.4 ± 10.1 (p = 0.032). These results indicate that peer education effectively enhances adolescents’ knowledge and empowerment, facilitating behavioral changes that contribute to the prevention of early marriage. The study highlights the importance of adolescent-centered interventions and peer-led programs in promoting reproductive health awareness and delaying marriage among at-risk youth. Implementing peer education as part of community-based programs can strengthen adolescent empowerment and reduce the prevalence of early marriage in the region.